2014
DOI: 10.1097/qad.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

Incorrect identification of recent HIV infection in adults in the United States using a limiting-antigen avidity assay

Abstract: Objectives To evaluate factors associated with misclassification by the limiting-antigen avidity (LAg-avidity) assay among individuals with long-standing HIV infection. Design Samples were obtained from the Multicenter AIDS Cohort Study (MACS), and AIDS Linked to the IntraVenous Experience (ALIVE) cohort (1089 samples from 667 individuals, 595 samples collected 2–4 years and 494 samples collected 4–8 years after HIV seroconversion). Paired samples from both time points were available for 422 (63.3%) of the 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 26 publications
4
31
0
Order By: Relevance
“…The recentness of infection was identified in each sample using the EIA-RI (IDE/V3) assay (20,24). Recent studies have shown that a combination of assays may improve the accuracy of the data (35)(36)(37)(38). Although we did not use a multiassay algorithm, our strategy which corrects the false recentness for any patient known to be at the AIDS stage, a major factor for misclassification, was shown to be relevant at a population level (20,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The recentness of infection was identified in each sample using the EIA-RI (IDE/V3) assay (20,24). Recent studies have shown that a combination of assays may improve the accuracy of the data (35)(36)(37)(38). Although we did not use a multiassay algorithm, our strategy which corrects the false recentness for any patient known to be at the AIDS stage, a major factor for misclassification, was shown to be relevant at a population level (20,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Using the same set of specimens from the ALIVE and MACS cohorts, the Bio-Rad Combo Avidity assay had a similar FRR to the LAg-Avidity assay, using a LAg-Avidity assay cutoff of 1.5 OD-n (FRR: 5.8% and 4.8%, respectively). 13 The same factors were associated with misclassification in multivariate analysis for these two assays: viral suppression (VL <400 copies/ml) and low CD4 cell count (<50 cells/mm 3 ). In another report, the third-generation Bio-Rad GS HIV-1/ HIV-2 Plus O EIA was modified for incidence testing using urea as the chaotropic agent, rather than DEA.…”
Section: Discussionmentioning
confidence: 92%
“…Low viral load (VL) (natural 10 or drug-induced 11 ), low CD4 cell count, 12,13 and HIV subtype D 14 are associated with misclassification by cross-sectional incidence assays. The performance of incidence assays can be characterized by two variables: the mean duration of recent infection (MDRI, the average amount of time individuals are considered recently infected for a given assay or algorithm), and the false recent rate (FRR, the frequency that individuals with long-term infection are misclassified as recently infected).…”
mentioning
confidence: 99%
“…Under a general framework for incidence estimation, two parameters are required (Kassanjee, McWalter & Barnighausen 2012): The Mean Duration of Recent Infection (MDRI) -the average time subjects spend 'recently' infected within some time post infection; and the FalseRecent Rate (FRR) -the probability that a subject who is infected for longer than will return a 'recent' result. While the FRR should ideally be zero, it is non-negligible for many currently available TRIs and is understood to vary by time and place (Busch, Pilcher & Mastro 2010;Hallett, Ghys & Barnighausen 2009;Kassanjee, Pilcher & Keating 2014;Le Vu, Pillonel & Semaille 2008;Longosz, Mehta & Kirk 2014;Mastro, Kim & Hallett 2010;Murphy & Parry 2008). The MDRI, typically required to be at least half a year for a TRI to begin to show promise (Incidence Assay Critical Path Working Group 2011), should ideally remain constant so that a once-calibrated TRI would be useful when transferred to other contexts.…”
Section: Introductionmentioning
confidence: 99%